The American smart power project towards the Arab Spring revolutions - Hammed, Karrar Noori (Tikrit Journal For Political Science, 2023)
The concept of smart power is one of the relatively recent concepts in international relations, and it represents an important axis of the axes of the study of power, as on the one hand, soft power is the new measure for any emerging power after it possesses hard power, mainly in the military and economic aspects. This provides the academic field with more focus on smart power and studying it as a means of managing crises peacefully without falling into armed conflicts by relying on soft power and realizing the importance of hard power as an essential element of power without neglecting one of them, in addition to realizing the shift in the nature of the political hegemony of the major countries recently as they turned from colonialism Or even military intervention and periods of agency wars that lead to soft cultural or economic dominance...etc.